On the performance techniques and emotional expression of the flute music “Prokofyev's flute sonata in D major” (Journal of Global Arts Studies, 2023)
Background: Sergei Sergeyevich Prokofiev created a large number of musical works throughout his life. His musical career can be divided into three periods: the Russian period, the foreign period, and the Soviet period, each with a different style of work. Purpose: This article takes Prokofiev's only sonata for the flute, "D Major Flute Sonata," as the research object, aiming to analyze the fragments of the work from the aspects of melody, musical form, and performance precautions. Methods: The first part analyzes the creative background of "Flute Sonata in D Major" using music score as a case study; The second part analyzes the structure of the work "Flute Sonata in D Major" and provides examples to explore the playing details and techniques; The third part focuses on the creative background and personal artistic style of the collaborator, and explores the emotional expression that runs through the entire D major Flute Sonata. Results: Through comparative analysis of the performance versions of "Flute Sonata in D Major", this study explores the control of music style, summarizes the experience and skills of excellent performers, and improves their performance level. Conclusion: The melody of the Flute Sonata in D major is not just a bunch of lines, but also follows the rules of harmony and counterpoint. Although this work is a late achievement of Prokofiev, it encompasses all the characteristics of his style, namely a fusion of classical and modern emotional expression, with a more striking rhythm and more intense emotions.
Keywords: Prokofiev; Flute sonata in D major; Melody; Emotional expression